2021
DOI: 10.1186/s12950-021-00276-6
|View full text |Cite
|
Sign up to set email alerts
|

Pellino1 promoted inflammation in lung injury model of sepsis by TRAF6/ NF-κB signal pathway

Abstract: Background This study was designed to investigate the role of Pellino1 in lung injury model of sepsis and its anti-inflammation mechanism. Method: C57BL/6 male mice (6–7 weeks old) and Pellino1−/− male mice were subjected to laparotomy followed by extracorporeal cecum mobilization and ligation. THP-1 cells were treated with 500 ng/ml of LPS for 4 h. Both mRNA and protein expression of Pellino1 was increased at time dependence in lung tissue of lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Although mediated by LPS, the Pellino family plays a different role in endotoxin tolerance in macrophages. Endotoxin tolerance abrogated Pellino1 induction by LPS in macrophages (69,71,72) but an enhanced expression of Pellino3 (79). Elevated transcription of TNFa and IL-6 driven by TLR2/4 and also increased expression of C-C motif chemokine ligand 5 (CCL5) driven by TLR4 were observed in Pellino3-deficient human myeloid leukemia mononuclear cells (THP-1) in response to TLR agonists (79).…”
Section: Pellino Family In Myd88-dependent Tlr Signalingmentioning
confidence: 98%
See 2 more Smart Citations
“…Although mediated by LPS, the Pellino family plays a different role in endotoxin tolerance in macrophages. Endotoxin tolerance abrogated Pellino1 induction by LPS in macrophages (69,71,72) but an enhanced expression of Pellino3 (79). Elevated transcription of TNFa and IL-6 driven by TLR2/4 and also increased expression of C-C motif chemokine ligand 5 (CCL5) driven by TLR4 were observed in Pellino3-deficient human myeloid leukemia mononuclear cells (THP-1) in response to TLR agonists (79).…”
Section: Pellino Family In Myd88-dependent Tlr Signalingmentioning
confidence: 98%
“…Pellino1 positively regulates the production of inflammatory factors in MyD88-dependent TLR signaling (69,70) as MyD88 deficiency hindered the expression of Pellino1, NF-kB, IL-1b, IL-6, Beclin-1, and cyclooxygenase-2 (COX-2) in a cerebral ischemia/reperfusion (I/R) mouse model (70). Pellino1 also positively regulates the MyD88-dependent pathway by promoting K63 linked polyubiquitination of IRAK1, TBK1, TRAF6, and TAK1 to active the MAPK and NF-kB signaling pathways via TLR2 and TLR4 pathway (69,71). Upon LPS stimulation, the expression of Pellino1 is upregulated (69,71,72), possibly by increasing levels of p65 and phosphorylated IKKa/b in microglia (73).…”
Section: Pellino Family In Myd88-dependent Tlr Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…TRAF6 is a key adaptor for TLR4/NF-κB signaling in regulating innate and adaptive immunity ( 43 , 44 ). Increasing evidence indicates that the TLR4/TRAF6 pathway is considered to be involved in the process of inflammation-related ALI ( 45 47 ). For example, Ding et al and Liu et al both demonstrated that the inhibition of TRAF6 alleviated the severity of inflammation and lung injury in an ALI mouse model ( 45 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that the TLR4/TRAF6 pathway is considered to be involved in the process of inflammation-related ALI ( 45 47 ). For example, Ding et al and Liu et al both demonstrated that the inhibition of TRAF6 alleviated the severity of inflammation and lung injury in an ALI mouse model ( 45 , 47 ). Inhibition of TRAF6 ubiquitination can attenuate TRAF6-mediated NF-κB activation and proinflammatory cytokine expressions ( 45 , 46 , 48 ).…”
Section: Discussionmentioning
confidence: 99%